LEVELS OF ANXIETY: A STUDY WITH ATHLETES OF INCOME IN THE SPORTS CONTEXT OF PARANÁ (Fiep Bulletin - online, 2011)
The aim of this study was to investigate the anxiety levels of athletes in revenue sports context Paraná. Specifically, we compared anxiety levels between genders of athletes. The subjects were 238 athletes and 110 (46%) were male and 128 (54%) female. The tools that have been used were: identification form, questionnaire competitive state anxiety (SCAT). The data collection was individual in JAP'S 2008. The association was analyzed with chi-square for trends and prevalence ratio with Poisson regression, considering p
Keywords: Anxiety; Sports; Gender